IMPACT OF COVID-19 LOCKDOWNS ON CLINICAL SKILLS AND MENTAL HEALTH OF NURSING UNDERGRADUATES IN SINDH, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Introduction: The COVID-19 pandemic severely disrupted global healthcare systems and profoundly affected nursing education. In Sindh, Pakistan, lockdowns and institutional closures restricted clinical placements, limiting opportunities for nursing students to gain practical skills. This study explores the impact of the pandemic on clinical learning, psychological stress, and perceived competence among nursing undergraduates across two nursing institutions in Sindh.Methodology: A descriptive cross-sectional study was conducted between 1st September 2022 and 25th November 2022, involving 266 nursing students selected through multistage cluster sampling. Data were collected using a structured questionnaire assessing clinical exposure, emotional well-being, and perceived competence. Statistical analysis included chi-square tests and Principal Component Analysis (PCA), with a 95% confidence level and 5% margin of error.Results: Among participants, 67.7% were aged 21–25, and 95.9% were unmarried. Overall, 73.3% reported that cancelled or suspended clinical placements adversely impacted their learning. Significant associations were found between clinical disruption and gender, marital status, and residence (p < 0.05), with female and hostel based students more affected. PCA identified two key stress dimensions: personal stressors (e.g., fear of infection, family risk) and systemic barriers (e.g., lack of PPE, inadequate clinical guidance). Only 36.8% felt confident in independently managing patients.Conclusion: The pandemic led to significant clinical learning gaps and emotional distress among nursing students. The findings emphasize the urgent need for high-fidelity simulation, mentorship, and integrated mental health support within nursing curricula. Strengthening disaster preparedness in academic institutions is vital to ensure future readiness and student well-being.